1999
DOI: 10.1152/jappl.1999.87.3.1035
|View full text |Cite
|
Sign up to set email alerts
|

Elite athletes and the gene for angiotensin-converting enzyme

Abstract: The deletion (D) allele of the gene for angiotensin-converting enzyme (ACE) is associated with higher plasma and tissue levels of the enzyme and has also been related to a variety of cardiovascular complications, particularly myocardial infarction. On the basis of indirect evidence, we hypothesized that inheritance of the D allele would contribute to elite athletic ability. Over a period of 4 yr, 120 Caucasian athletes who were national (Australian) representatives in sports demanding a high level of aerobic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
5
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 19 publications
4
81
5
2
Order By: Relevance
“…However, only a few specific genetic variants have been suggested to affect some of the phenotypes reflecting physical functioning. The findings from these and other studies have mostly been based on selected populations [i.e., young healthy males and elite athletes; Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999] and have not been consistent [Taylor et al, 1999;Rankinen et al, 2000a,b;Frederiksen et al, 2002], or the association was confined to subgroups within the study sample [Geusens et al, 1997]. With respect to physical functioning, various different phenotypes [e.g., self-report; Christensen et al, 2000], a proportion of fast-twitch and slow-twitch fibers in skeletal muscle biopsies [Simoneau and Bouchard, 1995], magnetic resonance imaging of muscle mass [Gibbons et al, 1998], and measurement of maximal aerobic power (VO 2-max ) [Sundet et al, 1994] have been used in different studies, all of which suggested a genetic component to physical functioning.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, only a few specific genetic variants have been suggested to affect some of the phenotypes reflecting physical functioning. The findings from these and other studies have mostly been based on selected populations [i.e., young healthy males and elite athletes; Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999] and have not been consistent [Taylor et al, 1999;Rankinen et al, 2000a,b;Frederiksen et al, 2002], or the association was confined to subgroups within the study sample [Geusens et al, 1997]. With respect to physical functioning, various different phenotypes [e.g., self-report; Christensen et al, 2000], a proportion of fast-twitch and slow-twitch fibers in skeletal muscle biopsies [Simoneau and Bouchard, 1995], magnetic resonance imaging of muscle mass [Gibbons et al, 1998], and measurement of maximal aerobic power (VO 2-max ) [Sundet et al, 1994] have been used in different studies, all of which suggested a genetic component to physical functioning.…”
Section: Introductionmentioning
confidence: 83%
“…Not many candidate genes associated with physical functioning have been identified. One suggestion has been a polymorphism in the gene encoding the Angiotensin Converting Enzyme, but the association was found only in small samples of young healthy males and elite athletes [Montgomery et al, 1998;Williams et al, 2000;Gayagay et al, 1998;Myerson et al, 1999], and not in all studies [Taylor et al, 1999;Rankinen et al, 2000a,b] and not among the elderly [Frederiksen et al, 2002]. A polymorphism in the gene encoding a receptor for vitamin D has been associated with grip strength in postmenopausal women, but only in a nonobese subgroup [Geusens et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…The D allele has also been associated with increased risk of hypertension, diabetic renal complications and cardiovascular complications. Some studies have shown an association between ACE and physical performance [17][18][19], and it has been proposed that there may be a similarity in metabolic features between hypoglycaemia and exercise [8,20,21], such that patients with type 1 diabetes and the DD genotype are at increased risk of severe hypoglycaemia compared with those with the II genotype [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have failed to identify any association between the ACE I/D polymorphism and elite human performance. Taylor, Mammote, Fallon, and Bockxmeer (1999) examined 120 Australian national athletes from sports deemed to demand a high level of aerobic fitness (hockey players, cyclists, skiers, track and field athletes, sweemers, rowers and gymnasts) and found no difference in ACE genotype and allele frequency compared with controls. Similarly, the cohort examined by Karjalainen, Kujala, Stolt, Mantysaari, Viitasalo, Kainulainen et al (1999) of 80 elite endurance athletes from Finnish national teams and one of the largest (192 athletes) studies by Rankinen, Wolphart, Simoneau, Maier-Lenz, Rauramaa, Rivera et al (2000) which also included skiers, long and middle distance runners, cyclists and biathlon, was also result in failure to demonstrate an association between elite athletes and the ACE genotype.…”
Section: The Implications Of Gene Therapy In the Field Of Sportmentioning
confidence: 99%